Composição nutricional de frutas da biodiversidade brasileira e seu emprego na alimentação escolar na Região Sudeste - Silva, Camila Pia Delgado da [UNIFESP] (2016)
The objectives of this study were to compile the nutritional composition data of five native fruit species from biodiversity and evaluate the inclusion of these and other fruit trees in school feeding in the Southeast region of Brazil. To survey the inclusion of fruit species was developed a structured, self-administered, and application through electronic form. To compile the literature search was made in the main available online scientific databases, using as avalaible reference the methodology INFOODS (International Network of Food Data Systems). Of all municipalities in the Southeast 187 agreed to participate and only 5.9% (n = 11) reported making a purchase of fruit species from biodiversity, which are the origin of family farming. The lack of coordination between the actors of the Programa Nacional de Alimentação Escolar was one of the main limiting factors for insertion of native biodiversity fruits on menus of school meals. It was observed that the field of sustainability and biodiversity are still unknown and challenging before the professionals who work in school feeding, since only 40.6% of the dietitians reported taking into account the biodiversity factor in the preparation of school meals menus. Another limiting informed by nutritionists was the lack of information of the nutritional composition of these fruits. The compilation of the nutritional composition data was performed from five species and gathered 24 publications, and the species: 1- Surinam cherry- (Eugenia uniflora L.); 2 Jussara (Euterpe edulis M.); 3- Jenipapo (Genipa americana L.); 4 Jabuticaba or Jaboticaba (Plinia cauliflora M.) and 5- Pink pepper (Schinus terebinthifoli). The ripe pulp Surinam cherry had higher concentrations of dietary fiber, pro-vitamin A and vitamin C, the other species. Additionally, the frozen pulp Surinam cherry was classified as excellent source of carotenoids (> 200 mcg / 100 grams of edible portion). The ripe pulp jussara showed high levels of lipids, dietary fiber, vitamin C and iron. The ripe pulp jenipapo showed intermediate levels of carbohydrate, vitamin C, ß carotene, lycopene and phenolic compounds when compared to other species without study. Three publications have been found on the nutritional composition of jabuticaba and no study has been obtained on the nutritional composition of the pink pepper species. Therefore it was concluded that despite the challenges to inclusion of fruit species biodiversity in school feeding, some municipalities in the Southeast are already making the purchase and offering these foods on school menus. Also, species such as Surinam cherry and jussara show nutritional value highlighted and has the potential for insertion in school